Studies on hepatic uptake of antigen. III. Studies of liver macrophage function in normal rats and following carbon tetrachloride administration. - Lloyd, R S (1975)
A technique of pronase digestion followed by density gradient centrifugation was used to study the morphology and phagocytic function of isolated rat liver macrophages in the normal rat and at varying times after the in vivo administration of carbon tetrachloride. Administration of the hepatotoxin results in a transient fall in the number of isolated macrophages. This deficit is corrected by a rapid influx of mononuclear cells from elsewhere in the animal which quickly differentiate into liver macrophages. Despite changes in the morphology of isolated macrophages, no evidence was found to suggest in vitro functional impairment of these cells. In vivo studies of intrahepatic shunting showed that this became a significant phenomenon 6 hours after the administration of the hepatotoxin. The enhanced antibody response to sheep red cells which occurs after carbon tetrachloride administration appears to be due to a series of events in which the decrease in the number of liver macrophages is an early significant factor, while intrahepatic shunting is a major contributing factor at a later time.